2000
DOI: 10.1038/sj.jhh.1000984
|View full text |Cite
|
Sign up to set email alerts
|

Insulin and blood pressure responses to changes in salt intake

Abstract: In this study we evaluated the role of insulin in hypertension and on salt sensitivity. The study was conducted in 47 consecutive patients attending the Center for the Detection and Treatment of Cardiovascular and Metabolic Risk factors. The relationships between fasting and post-glucose load insulin levels and the blood pressure (BP) responses to changes in salt intake, were investigated. No correlation was observed between fasting or 2-h post-load insulin levels and mean BP (MBP), systolic BP (SBP) or diasto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…However, it is not clear whether in vivo Ang II or cyclical stretch or both are involved in the augmented oxidative stress observed in the 2K1C mice. In a hypertension rat model of infused Ang II, was demonstrated that this peptide, but not blood pressure is responsible for ROS production (Cubeddu et al, 2000).…”
Section: K1c Hypertension Affects Bone Marrow Cellsmentioning
confidence: 99%
“…However, it is not clear whether in vivo Ang II or cyclical stretch or both are involved in the augmented oxidative stress observed in the 2K1C mice. In a hypertension rat model of infused Ang II, was demonstrated that this peptide, but not blood pressure is responsible for ROS production (Cubeddu et al, 2000).…”
Section: K1c Hypertension Affects Bone Marrow Cellsmentioning
confidence: 99%
“…The present study has been performed to explore the influence of SGK1 on renal function and systolic blood pressure during a high-fat and high-salt diet, both of which have been shown to favor an increase in blood pressure (13,20,21,27,34,41,44,53,59). Surprisingly, lack of SGK1 does not affect systolic blood pressure after a high-fat diet alone, but it completely abrogates the increase in systolic blood pressure after additional high-salt treatment.…”
mentioning
confidence: 99%
“…Similarly, no association was found between fasting or post-load insulin and systolic or diastolic BP in a healthy Hispanic population under low and high salt intake conditions. 15 A major problem with most of these studies is the poor stratification of the study patients. 5,[11][12][13][14] The presence of confounding variables such as older age, obesity, visceral or abdominal fat accumulation, salt sensitivity, dyslipidaemia and others, complicates the interpretation of the results.…”
Section: Journal Of Human Hypertensionmentioning
confidence: 99%